2021
DOI: 10.1186/s12876-021-02031-w
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for adverse events associated with endoscopic retrograde cholangiopancreatography in patients with surgically altered anatomy: a retrospective study

Abstract: Introduction Endoscopic retrograde cholangiopancreatography (ERCP) is considered to be a challenge in patients with surgically altered anatomy. We aimed to identify the risk factors of ERCP-related adverse events in patients with surgically altered anatomy in our center. Methods We included patients with surgically altered anatomy who underwent ERCP between April 2017 and December 2020 at our center. Clinical characteristics and outcomes were analy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
2
1
Order By: Relevance
“…This high difference might be attributed to our study Gastroenterology and Hepatology centre is a tertiary training centre that received the more complicated cases from different Iraqi hospitals last year in addition to factors related to the experience of Physicians and the health status of patients received. However, our study's post-ERCP complications rate is lower than that of Chen et al (24) study in China, which found that post-ERCP adverse events occurred in 31 (25.6%) patients. The ERCP is applied in highvolume and low-volume centres and by physicians of variable experiences in addition to the gradual training of physicians to acquire safe and effective ERCP (25) .…”
Section: Discussioncontrasting
confidence: 87%
“…This high difference might be attributed to our study Gastroenterology and Hepatology centre is a tertiary training centre that received the more complicated cases from different Iraqi hospitals last year in addition to factors related to the experience of Physicians and the health status of patients received. However, our study's post-ERCP complications rate is lower than that of Chen et al (24) study in China, which found that post-ERCP adverse events occurred in 31 (25.6%) patients. The ERCP is applied in highvolume and low-volume centres and by physicians of variable experiences in addition to the gradual training of physicians to acquire safe and effective ERCP (25) .…”
Section: Discussioncontrasting
confidence: 87%
“…However, the two-stage procedure is complex and the success rate for one-stage TASR is low [ 14 , 15 ]. The technical success rate and clinical success rate were as high as 100% and 92.3%, respectively, in our evaluation of simplified single-session TASR and the incidence of adverse events was lower (15.4%) than that for ERCP (25.6%) [ 21 ]. We consider that the key to improving the technical success of simplified single-session TASR depends on a simplified process and the application of a 0.035-inch guide wire and co-axial cystotome.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, postoperative adhesions, strong curvature of the intestine, long afferent loops, individual surgical peculiarities, and different distances from defined marks impede the procedural success. The three mayor steps in successful ERCP in patients with altered anatomy include reaching the papilla or biliodigestive anastomosis, cannulation of the duct, and finally performing the planned intervention [6].…”
Section: Endoscopic Retrograde Cholangiopancreaticographymentioning
confidence: 99%